Implementation Of The Science Learning Model To Improving Students’ Scientific Argumentation Skills: A Review - Syuzita, Amalia (Balai Publikasi Indonesia, 2023)
Argumentation ability is one of the main goals of learning science because students who study science must know scientific explanations about natural phenomena, use them to solve problems and be able to understand other findings they get. This study is a Literature Review article which aims to identify the most effective learning models to improve students' scientific argumentation skills in science learning. A search of the literature study articles obtained twenty-five articles that met the inclusion criteria and were relevant for review. The results of the literature study show that one of the most effective learning models in improving students' scientific argumentation skills in science isArgument Driven Inquiry with approachsocio scientif issues. The highest score range is 80-90 based on the research results contained in the 10 articles that have been analyzed. While the lowest range is in the 40-50 range found in 1 article that has been analyzed.